Role of defense/immunity proteins in non-obstructive azoospermia: insights from gene expression and single-cell RNA sequencing analyses - Abroudi, Ali Shakeri; Azizi, Hossein; Djamali, Melika; Abdullah, Hewa Khalid; Qorbanee, Ali; Skutella, Thomas (Reproductive sciences, 2025)
Non-obstructive azoospermia (NOA) is a severe form of male infertility characterized by a complete absence of sperm in the ejaculate due to impaired spermatogenesis. While genetic and hormonal factors are known contributors, recent evidence highlights the role of immune dysregulation in NOA pathophysiology. Defense/immunity proteins play a crucial role in maintaining testicular immune homeostasis, but their aberrant expression may contribute to spermatogenic failure. This study analyzed gene expression data from multiple datasets to identify immune-related genes significantly altered in NOA, including IFITM1, CES1, MR1, LSAMP, PRB2, CARD8, and PECAM1. Differential expression analysis revealed upregulation of IFITM1 and PECAM1 and downregulation of CES1, MR1, LSAMP, PRB2, and CARD8, suggesting immune imbalance and oxidative stress contribute to NOA pathogenesis. Additionally, single-cell RNA sequencing confirmed their differential expression in distinct testicular cell populations. Our findings suggest that immune-related pathways, including cytokine signaling, antigen processing, and oxidative stress response, may contribute to NOA pathogenesis. Targeting these molecular pathways could provide novel therapeutic strategies for improving reproductive outcomes in affected individuals.